Pelatihan Pebuatan Susu Kedelai Bagi Masyarakat Desa Cinta Raja Kecamatan Secanggang Kabupaten Langkat - Danu Prayuda; Pupu Muhidin; Azizi Miarti; Ali Mukhlis AR; Enda Lovita Pandiangan (Fusion: Jurnal Pengabdian kepada Masyarakat, 2024)
Milk is the first food a baby knows through breast milk (ASI). The public is aware that the quality of breast milk issuperior to cow's milk, formula milk and powdered milk. Milk is a food ingredient that is composed of foodsubstances in balanced proportions. From another angle, milk can also be viewed as a raw material that containsimportant food sources. Soy milk is one of the processing products which is the result of extraction from soybeans.Soy milk protein has an amino acid composition that is almost the same as cow's milk. So soy milk is often used asa substitute for cow's milk for those who are allergic to animal protein. Soy milk is a highly nutritious drink,especially because of its protein content. Apart from that, soy milk also contains carbohydrate fats, calcium, phosphorus, iron, vitamin A and vitamin B complex except B12 and water. Students from KKN Post IX CintaRaja Village, which was held on Tuesday, March 5 2024 in the office hall of Cinat Raja Village, Seacanggang subdistrict,carried out training in making soy milk. The qualitative descriptive research method is a method used byresearchers to discover knowledge or theories regarding research at a certain time. The result of this trainingactivity is that the people of Cinta Raja Village gain knowledge and understanding about the advantages anddisadvantages of consuming soy milk. Community service in the form of training has provided the community witha new understanding of soy milk, so that the results of this training open up business opportunities, understandstunting prevention, and provide knowledge about soy milk.